Heads we win, tails you lose: Is there equity in Islamic equity funds? - Mustaffa Kamil, Nazrol Kamil; Alhabshi, Syed O.; Bacha, Obiyathulla I.; Masih, Mansur (Elsevier, 2014)
We made the first estimate of the proportion of fund alpha statistically attributable to luck rather than skill for a sample of Malaysian Islamic equity funds. Broadly, the funds do not outperform market benchmarks. In the limited instances where performance is superior, based on a contemporary methodology, as much as 47% of the observed positive fund alpha is statistically attributable to luck. Thus, at 5% significance level, we find only 1.95% of our funds to be genuinely skilled. Our findings raise questions regarding the equitability of these funds levying fixed fees, making a case for potential innovation in fund remuneration structure.